The Influence of Human Capital and Time Budget Pressure on Remote Audit Survey KAP Central Java DIY - Astuti, Dewi Saptantinah Puji; Ratnawati, Tri (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
The purpose of this study was to find out how the influence of exogenous variables (Human Capital and Time Budget Pressure on Remote audit. Data was obtained by distributing questionnaires to respondents, namely auditors at Public Accounting Firms in Central Java and Yogyakarta. The results of research for direct influence stated that all hypotheses were accepted. The analytical tool used is SPSS Suggestions for further researchers to develop research by adding the internal auditor’s role variable and the number of findings produced by auditors in the field.